2017
DOI: 10.1097/gme.0000000000000741
|View full text |Cite
|
Sign up to set email alerts
|

Age at natural menopause genetic risk score in relation to age at natural menopause and primary open-angle glaucoma in a US-based sample

Abstract: Objective Several attributes of female reproductive history, including age at natural menopause (ANM), have been related to primary open-angle glaucoma (POAG). We assembled 18 previously reported common genetic variants that predict ANM to determine their association with ANM or POAG. Methods Using data from the Nurses’ Health Study (7,143 women), we validated the ANM weighted genetic risk score in relation to self-reported ANM. Subsequently, to assess the relation with POAG, we used data from 2,160 female P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…The beneficial effects of endogenous or exogenously applied 17β-estradiol (E2) for eye health have been shown by basic science studies [1][2][3][4][5] and epidemiological observations [6][7][8]. Our interest in this regard stems from an unmet medical need for ocular neuroprotection [3,9].…”
Section: Introductionmentioning
confidence: 99%
“…The beneficial effects of endogenous or exogenously applied 17β-estradiol (E2) for eye health have been shown by basic science studies [1][2][3][4][5] and epidemiological observations [6][7][8]. Our interest in this regard stems from an unmet medical need for ocular neuroprotection [3,9].…”
Section: Introductionmentioning
confidence: 99%
“… 47 The number of studies reporting each of these subtypes individually did not make a subanalysis realistic in this review, although an effort was made to do so. A recent genetic risk score of 18 single nucleotide polymorphisms strongly associated with the age at natural menopause (explaining 4.8% of the variation in age at natural menopause) was not found to be associated with POAG, 48 suggesting no likely underlying genetic association for the findings from the included observational studies. Interestingly, 1 included study found that individuals who underwent surgically induced menopause (via bilateral oophorectomy) before the age of 43 had 1.6 times the risk of glaucoma (broadly defined) compared with a referent group of age-matched women who did not undergo oophorectomy (OR, 1.6; 95% CI, 1.15–2.23).…”
Section: Discussionmentioning
confidence: 90%